2016
DOI: 10.18632/oncotarget.13539
|View full text |Cite
|
Sign up to set email alerts
|

Identification of aberrantly expressed glycans in gastric cancer by integrated lectin microarray and mass spectrometric analyses

Abstract: Cancer progression is usually associated with alterations of glycan expression patterns. Little is known regarding global glycomics in gastric cancer, the most common type of epithelial cancer. We integrated lectin microarray and mass spectrometry (MS) methods to profile glycan expression in three gastric cancer cell lines (SGC-7901, HGC-27, and MGC-803) and one normal gastric epithelial cell line (GES-1). Significantly altered glycans were confirmed by lectin staining and MALDI-TOF/TOF-MS. The three cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…It has been well documented that Tn antigen is one of the most expressed tumour antigen found in many human cancers, such as colon, breast, cervix, stomach and skin . Many studies have established an association of Tn antigen expression with cancer progression and metastasis and poor outcome .…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that Tn antigen is one of the most expressed tumour antigen found in many human cancers, such as colon, breast, cervix, stomach and skin . Many studies have established an association of Tn antigen expression with cancer progression and metastasis and poor outcome .…”
Section: Discussionmentioning
confidence: 99%
“…All four lectins showed binding specificity to high-mannose glycan structures, thereby the glycans were significantly increased in moderately-differentiated components compared with well-differentiated components in HCC. NPA-one of the elevated lectins that binds high-mannose glycans-has been reported to be increased in gastric cancer cell lines [32]. Therefore, we performed NPA staining to confirm elevated high-mannose glycan expression and demonstrated that increased high-mannose glycans expression was associated with decreased MGAT1 expression.…”
Section: Discussionmentioning
confidence: 93%
“…A lectin/glyco-antibody microarray performed on sera from 22 pancreatic cancer sera, discriminated cancer patients from other diseases (35 chronic pancreatitis, 37 diabetes) and normal controls (89 controls), by a 70% increase inthe response of serum α1β-glycoprotein to SNA ( Sambucus nigra agglutinin) [121]. Using a 45-immobilized lectin microarray, the cell surface glycan changes occurring during the malignant transformation of endometrium, were investigated [122].…”
Section: Tn/t-specific Lectins For Cancer Diagnosis/prognosismentioning
confidence: 99%